Strategi Camat Dalam Memanage Dan Meningkatkan Sumber Daya Manusia Di Kecamatan Picung - Ahmad Daerobi; Susi Susanti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Human resources are important for the development of a country that wants its country to develop or progress. Human resource management is a part of management science that focuses its attention on regulating the role of human resources in an organization. In achieving its goals, of course an organization needs human resources as system managers. In order for this system to run, of course in its management it must pay attention to several important aspects such as training, development, motivation and other aspects. Human resources are a very vital organizational asset, therefore their role and function cannot be replaced by other resources. No matter how modern the technology is used, no matter how much funds are in the archives. However, without professional human resources, everything becomes meaningless. To create quality human resources, various specific training is needed to achieve the desired goals, therefore we have oriented this government science journal so that readers can find out what factors can improve the quality of human resources today